Efficacy and prognostic factors of second transurethral resection for non-muscle-invasive bladder cancer - AO Yangkun; LUO Weiming; RAN Qiang (陆军军医大学学报)
‍Objective‍　‍To investigate risk factors for residual lesions after initial transurethral resection of bladder tumors (TURBT) and risk factors for tumor recurrence after second TURBT in patients with non-muscle-invasive bladder cancer (NMIBC) in order to provide reference for clinical management. Methods‍　‍A case-control study design was adopted to include 120 NMIBC patients who underwent initial TURBT and then second surgery within 2~8 weeks in our department from January 2017 to January 2025. Based on the presence of residual lesions after the initial TURBT or not, the patients were divided into a residual lesion group (n=34) and a non-residual lesion group (n=86). Chi-square test and multivariate logistic regression analysis were performed to identify potential risk factors for residual lesions following the initial TURBT. Univariate and multivariate Cox regression models were used to analyze potential risk factors for tumor recurrence after the second TURBT. Results‍　‍The residual lesion rate after initial TURBT was 28.33%. Chi-square test analysis revealed that tumor stage T1 (Chi-square=5.756, P=0.016) and broad tumor base (Chi-square=4.331, P=0.037) were factors influencing residual lesions after initial TURBT. Multivariate logistic regression analysis identified tumor stage T1 (OR=3.047, 95%CI: 1.128~8.226, P=0.028) as an independent risk factor for residual lesions after initial TURBT. The tumor recurrence rate after second TURBT was 17.5%. Multivariate Cox regression analysis identified tumor stage T1 (OR=4.258, 95%CI: 1.248~14.532, P=0.021), intravesical chemotherapy instillation after second TURBT (OR=3.539, 95%CI: 1.284~9.752, P=0.015), history of urinary system tumors (OR=3.002, 95%CI: 1.145~7.873, P=0.025) and high platelet-to-lymphocyte (PLR) ratio (OR=2.798, 95%CI: 1.115~7.023, P=0.028) as independent risk factors for tumor recurrence after second TURBT. Conclusion‍　‍Tumor stage T1 and broad tumor base are risk factors for residual lesions after initial TURBT, while tumor stage T1, intravesical chemotherapy instillation after second TURBT, history of urinary system tumors and high PLR ratio are risk factors for tumor recurrence after second TURBT. Comprehensive analysis on above 4 indicators can effectively assess the risk of tumor recurrence in NMIBC patients following second TURBT, and timely early medical intervention is beneficial for improving patient outcomes.